Socio-demographic profile in purchasing natural and synthetic functional foods in Malaysia - Phuah, K. T.; Rezai, Golnaz; Mohamed, Zainal Abidin; Shamsudin, Mad Nasir (International Association of Computer Science and Information Technology Press, 2015)
Functional foods represent one of the most interesting areas of research and innovation in the food industry. There are commercialized functional products in Malaysian market presently. Although the consumption of functional foods is increasing, relatively little is known about how consumers perceive these products and their buying frequency towards natural and synthetic functional foods in Malaysia. Therefore, the purpose of this study is to determine the relationship between socio-demographic variables and consumers’ knowledge and buying frequency towards Natural and synthetic functional foods. Systematic random sampling was used in this study and 2004 households are interview by using structure questionnaire in Malaysia. Descriptive analysis and chi-square analysis were used in this study. The result shows that education level, area, income level, age and child under 18 years old have significant relationship with their knowledge to differentiate natural and synthetic functional foods.Moreover, the result also shows that marital status, area, education level, household size, age, income level and child under 18 years old have significant relationship with their purchasing behavior towards functional foods.